ANALISIS MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN DAN ABNORMAL RETURN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2012 - Yustina Triyani (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2015)
This study aimed to analyze the differences in financial performance and abnormal returns before and after the merger and acquisition of the companies listed in Indonesia Stock Exchange in 2009-2012. Financial performance used in this study include: Return on Equity (ROE), Net Profit Margin (NPM), and Operating Profit Margin (OPM). Agency theory emerged in the agency relationship between the principal (investor) and the agent (manager) are bound in a contract. The essence of this relationship is the separation of ownership (in the investor) and control (at the manager). Investors have the expectation that the manager will generate a return of the money they invest. Therefore, a good contract between the investor and the manager is a contract that is able to explain the specification of what should be done by a manager in managing the funds of investors and the specification of the division of returns between managers and investors. Data collection method which used is the method of observation. Data retrieval technique which was used is purposive sampling in which the authors take the data across public companies listed on the Indonesia Stock Exchange (IDX) conducting mergers and acquisitions in the period 2009-2012. Test for normality using the Kolmogorov-Smirnov test. If the data were tested normal distribution, then the data are tested using a paired sample t-test, whereas if the data are not normally distributed, then tested using the Wilcoxon Signed Ranks Test to answer the hypothesis. Both of these different test methods using a significance level of 95%. The test results showed ROE of 0009, NPM for 0002, OPM at 0.0155. because the test results ROE, NPM, and OPM less than 0.05 means ROE, NPM, and OPM significant effect on mergers and or acquisitions. While abnormal return of 0.2845 which means abnormal returns no significant effect on mergers and or acquisitions. The results of this study concluded that there is sufficient evidence of financial performance increases after the merger and or acquisition, but there is not enough evidence of abnormal returns after a merger or acquisition and increased than before the merger and or acquisition.